Pemulihan Kadar Glikogen Serta Peningkatan Konsumsi Glukosa dan Trigliserida Saat Aktivitas Fisik Pascapemberian Ekstrak Kulit Buah Manggis (GLYCOGEN RECOVERY AND INCREASE CONSUMPTION OF GLUCOSE AND TRIGLYCERIDE DURING PHYSICAL ACTIVITIES AFTER ADMINISTRA - Arsana, I Nyoman; Juliasih, Ni Ketut Ayu (Jurnal Veteriner; Vol 17 No 1 (2016), 2016)
This study was aimed to investigate the effect of mangosteen rind on the glycogen recovery of themuscle and the liver, and the glucose and the triglyceride consumption during physical activities. ARandomized Block Design was applied with four treatments: control (K), physical activity (KF), physicalactivity and extract (FE),extract (E). The extract dosage was 400 mg/kg bodyweight/day administered forfour weeks. The assessed variables were the muscle glycogen, the liver glycogen, the blood glycogen, and thetriglyceride in the end of the treatments. Based on the research results, it was found that the muscleglycogen, the blood glucose, and the triglyceride of the E group were lower, whereas the liver glycogen wassignificantly higher than that of the control (K) group. The means of the muscle glycogen, the liver glycogen, the blood glucose, and the triglyceride of the control (K) group were respectively 0.41±0,01 ?g/25mg, 0.22±0.01?g/25mg, 85.89±2.45 mg/dL, and 32.00±3.38 mg/dL whereas of the E group were 0.39±0.01 ?g/25mg,0.26±0.02 ?g/25mg, 75.84±2.29 mg/dL, and 23.39±2.08 mg/dL. After a physical activity of the KF group,the muscle glycogen and the liver glycogen decreased, however the blood glucose and the triglycerideincreased significantly if compared to those of the control (K) group. The means of the KF group wererespectively 0.14±0.01 ?g/25mg, 0.09±0.01 ?g/25mg, 164.73±11.07 mg/dL, and 66.31±2.96 mg/dL. Afterthe administration of the extract to the FE group, their muscle and liver glycogen increased, but the glucoseand the triglyceride decreased more significant than those of the KF. The means of the FE group were0.35±0.01 ?g/25mg, 0.19±0.01 ?g/25mg, 107.05±7.79 mg/dL, and 40.00±2.30 mg/dL respectively. Theseresults showed that during the physical activities, the energy was taken from the muscle and liver glycogen,whereas the glucose and the triglyceride were mobilized into the blood as the reserve source. After theextract administration, the source of the energy was taken back to the muscle and the liver, and then theglucose and the triglyceride were utilized. The compound within the extract is assumed to have influenceon the activities of the enzymes involved in the metabolism of the carbohydrate and the fat. It can beconcluded that the mangosteen rind extract recovers the muscle and the liver glycogen as well as increasingthe glucose and the triglyceride consumption during the physical activities.
Keywords: mangosteen (Garcinia mangostana L); glycogen; glucose; triglyceride; physical activity